Growing Oxide Nanowires and Nanowire Networks by Solid State Contact Diffusion into Solution‐Processed Thin Films. Issue 43 (13th September 2016) - Glynn, Colm; McNulty, David; Geaney, Hugh; O'Dwyer, Colm
Abstract : New techniques to directly grow metal oxide nanowire networks without the need for initial nanoparticle seed deposition or postsynthesis nanowire casting will bridge the gap between bottom‐up formation and top‐down processing for many electronic, photonic, energy storage, and conversion technologies. Whether etched top‐down, or grown from catalyst nanoparticles bottom‐up, nanowire growth relies on heterogeneous material seeds. Converting surface oxide films, ubiquitous in the microelectronics industry, to nanowires and nanowire networks by the incorporation of extra species through interdiffusion can provide an alternative deposition method. It is shown that solution‐processed thin films of oxides can be converted and recrystallized into nanowires and networks of nanowires by solid‐state interdiffusion of ionic species from a mechanically contacted donor substrate. NaVO3 nanowire networks on smooth Si/SiO2 and granular fluorine‐doped tin oxide surfaces can be formed by low‐temperature annealing of a Na diffusion species‐containing donor glass to a solution‐processed V2 O5 thin film, where recrystallization drives nanowire growth according to the crystal habit of the new oxide phase. This technique illustrates a new method for the direct formation of complex metal oxide nanowires on technologically relevant substrates, from smooth semiconductors, to transparent conducting materials and interdigitated device structures. Abstract : Contact interdiffusion allows solid‐state ternary metal oxide nanowire growth directly from thin film‐coated surfaces and devices. Formation and crystallization of complex oxide nanowires on surfaces and devices is facilitated between a solution‐processed surface oxide film and contacted glass containing a diffusion species. Contact interdiffusion opens up a new avenue for oxide nanowire research and application to a variety of surfaces and substrates.